Service Level Agreement Violation Detection in Multi-cloud Environment using Ethereum Blockchain - Neeraj, N.K; Nellikeri, Aditya; Varun, P; Reddy, Santosh; Shanbhag, Mangesh; Narayan, Dg; Husain, Altaf (2023 International Conference on Networking and Communications (ICNWC), 2023)
With the advancement of cloud computing technologies, it is necessary to maintain quality of service, for which service level agreements (SLAs) are one of the ways to improve this. A significant part of revenue will be contributed by the use of on demand resources (compute, network or storage) provided by this cloud service providers (CSP). Service level agreement (SLA) plays a key role in maintaining quality of services (QoS) of these on demand resources. The CSP enforces the SLA, by utilizing machine-generated logs to monitor machine performance. Additionally, some consumers may monitor resource performance themselves to ensure it meets their standards. This approach not only leads to traction between both CSP and cloud service consumers (CSC), but also leads to a duplication of the effort. The aim of this work is to create a system that is distributed in nature and could be trusted by both CSP and the consumer. The paper provides solution using a public blockchain and log based algorithm that evaluates resource performance based on several SLA criteria accepted by the CSP and consumers. If the system's performance falls below a certain level, the CSC will be intimated through logs. This motivates the consumer to spend more money on the resources and compels the CSP to keep the number of SLA violations to a minimal. A web application with a blockchain as the back-end is used to monitor SLA violations and the compensation procedure. Finally, a multi-node ethereum blockchain network is used to conduct a performance analysis of the suggested solution.